Improving Environmental Quality Through Willingness To Pay: Analysis of Ecotourism Visitors to Bandengan Beach, Jepara - Prambudi, Bono; Darodjatun, MAS Sridjoko (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyse the willingness of visitors who deliberately come to pay to help in managing and organising Bandengan Beach ecotourism as well as possible and to analyse the estimation or amount of entrance ticket levy in Bandengan Beach ecotourism area in an effort to maintain the environment. Respondents in this study were 54% female and 46% male. The respondents through questionnaires that were answered and processed, provided information that the value of the cost that is considered reasonable for visitors is Rp. 5,949, - per person. The results of this study indicate that the income variable, age variable and education variable, do not influence the dependent variable, namely willingness to pay. While the frequency of visits and knowledge variables have an influence on the dependent variable of willingness to pay. . Keywords: Tourism, Willingness to Pay, Environmental Quality